Leptomeningeal disease and brain control after postoperative stereotactic radiosurgery with or without immunotherapy for resected brain metastases. Issue 12 (23rd December 2021) - Minniti, Giuseppe; Lanzetta, Gaetano; Capone, Luca; Giraffa, Martina; Russo, Ivana; Cicone, Francesco; Bozzao, Alessandro; Alongi, Filippo; Nicosia, Luca; Fineschi, Gioia; Marchetti, Luca; Tufo, Tommaso; et al.
Abstract : Purpose: Immunotherapy has shown activity in patients with brain metastases (BM) and leptomeningeal disease (LMD). We have evaluated LMD and intraparenchymal control rates for patients with resected BM receiving postoperative stereotactic radiosurgery (SRS) and immunotherapy or postoperative SRS alone. We hypothesize that postoperative SRS and immunotherapy will result in a lower rate of LMD with acceptable toxicity compared with postoperative SRS. Patients and methods: One hundred and twenty-nine patients with non-small-cell lung cancer (NSCLC) and melanoma BM who received postoperative fractionated SRS (fSRS; 3×9 Gy) in combination with immunotherapy or postoperative fSRS alone for completely resected BM were retrospectively evaluated. The primary endpoint of the study was the rate of LMD after treatments. The secondary endpoints were local failure, distant brain parenchymal failure (DBF), overall survival (OS), and treatment-related toxicity. Results: Sixty-three patients received postoperative SRS and immunotherapy, either nivolumab or pembrolizumab, and 66 patients received postoperative SRS alone to the resection cavity. With a median follow-up of 15 months, LMD occurred in 19 patients: fSRS group, 14; fSRS and immunotherapy, 5. The 12-month LMD cumulative rates were 22% (95% CI 14% to 37%) in the fSRS group and 6% (95% CI 2% to 17%) in the combined treatment group (p=0.007). Resection cavity control was similar between the groups, whereas DBF and OS were significantly different; the 1-year DBF rates were 31% (95% CI 20% to 46%) in the fSRS and immunotherapy group and 52% (95% CI 39% to 68%) in the fSRS group; respective OS rates were 78% (95% CI 67% to 88%) and 58.7% (95% CI 47% to 70%). Twenty-two patients undergoing postoperative fSRS and immunotherapy and nine subjected to postoperative fSRS experienced treatment-related imaging changes suggestive of radiation-induced brain necrosis (p=0.02). Conclusions: Postoperative fSRS in combination with immunotherapy decreases the incidence of LMD and DBF in patients with resected BM from NSCLC and melanoma as compared with fSRS alone, reducing the rate of neurological death and prolonging survival.